Influence of active constrained layer damping on the coupled vibration response of functionally graded magneto-electro-elastic plates with skewed edges - M. Vinyas; D. Harursampath; T. Nguyen-Thoi (Defence Technology, 2020)
This article makes the first attempt in assessing the influence of active constrained layer damping (ACLD) treatment towards precise control of frequency responses of functionally graded skew-magneto-electro-elastic (FGSMEE) plates by employing finite element methods. The materials are functionally graded across the thickness of the plate in terms of modest power-law distributions. The principal equations of motion of FGSMEE are derived via Hamilton’s principle and solved using condensation technique. The effect of ACLD patches are modelled by following the complex modulus approach (CMA). Additionally, distinctive emphasis is laid to evaluate the influence of geometrical skewness on the attenuation capabilities of the plate. The accuracy of the current analysis is corroborated with comparison of previous researches of similar kind. Additionally, a complete parametric study is directed to understand the combined impacts of various factors like coupling fields, patch location, fiber orientation of piezoelectric patch in association with skew angle and power-law index.